The influence of social networks on poor decisions and bad habits related to the oral health of adolescents and adults: An integrative literature review (Research, Society and Development, 2021)
With the increase in the production of digital content on dentistry there has also been an increase in the dissemination of habits and the use of harmful accessories to maintain satisfactory oral health and its influence mainly on adolescents and young adults. The aim of this paper is to identify what is the impact on the oral health of adolescents and adults who make use of some of the accessories and harmful habits such as activated charcoal, oral piercing and fake appliances that are propagated by social media. This is an integrative literature review carried out under the parameters of the PRISMA strategy for systematic reviews, searching the databases PUBMED, Scielo and Biblioteca Virtual em Saúde (BVS). After applying the inclusion and exclusion criteria, 13 articles were selected for qualitative analysis. Several consequences can be caused by the use of activated carbon, oral piercing and false appliances, among which are dental caries, periodontal disease, non-carious lesions, mucosal lesions and bacterial and fungal infections. It can be seen that although there are many advantages in the use of social networks, many influences can be negative, especially with regard to health, especially when the content is not disclosed exclusively by people with scientific preparation for this purpose. More studies need to be conducted, seeking increasingly reliable levels of evidence, to understand the exact harm and severity that the use of these habits and accessories can cause on oral health.